Statistical - Spatial Analysis of the Core of Siberian High Pressure System Period 1955-2014) - daryosh yarahmdi; asadollah khoshkish; Mustafa Karampour; Ismail Ahmadi (تحقیقات کاربردی علوم جغرافیایی)
One of the Siberian high pressure system is the Earth climate system, atmospheric important. The purpose of this study, analysis of core changes Siberian high pressure system in the period mentioned. To identify the core spatial variations in the timeframe mentioned data, daily sea level pressure and temperature of the earth's surface with a resolution of 2.5 degrees within the space of 30 to 65 degrees north latitude and 130 degrees east longitude from the database 45 to NOAA NCEP / NCAR for the cold was extracted. The core of the GIS spatial data analysis system and two separate zones and point to output six decades was ten years old and were analyzed. To study the process of change, determine the direction of the trend, type and timing of changes in temperature and pressure of the core of the system the test of Mann-Kendal is used. Comparison between the first and sixth decades 60-year period showed that the core in January from the East to the West and in October and March from the North East to the South West from the Balkhash Lake to Baikal there has been a significant shift. Results also showed that during the same period the Siberian High central pressure was reduced in January while the land surface temperatures in January showed a significant upward trend. Unlike the months of October and January, in March the central pressure had few mutations but no trend was observed. However, during this month the Earth's surface temperature has increased significantly during thementioned period.